Pendampingan Penyusunan Kurikulum Peduli Hak Anak Dan Hak Asasi Manusia Pada PAUD Basmala - Ali Masykur; Sukiram Sukiram (LP2M of Institute for Research and Community Services - UIN Walisongo, 2018)
This paper tries to elaborate on the assistance efforts to create a curriculum that is child-friendly and human rights-friendly. Assistance is done at PAUD of Basmala Grobogan. The child is the future determinant of a nation. The guarantee of the rights and protection of children is to ensure the fulfillment of the rights of the child, in order to live, grow, develop and participate optimally in accordance with human nature and dignity, and get protection from violence and discrimination for the realization of quality Indonesian children, morality and prosperity absolutely necessary to ensure a good growth mentally, spiritually and socially. Early childhood education provides a basic foundation and character formation in the golden age of children in life. A good curriculum and learning method and ensuring the rights of children and human rights are absolutely given for the child's future in the form of non-discrimination, the best interests of the child, survival and development, respect for children's opinions. Tulisan ini mencoba menguraikan upaya pendampingan pembuatan kurikulum yang ramah hak anak dan hak asasi manusia. Pendampingan dilakukan di PAUD Basmala Grobogan. Anak adalah penentu masa depan suatu bangsa. Jaminan hak dan perlindungan anak adalah untuk menjamin terpenuhinya hak-hak anak, agar dapat hidup, tumbuh, berkembang dan berpartisipasi secara optimal sesuai dengan kodrat dan martabat kemanusiaan, serta mendapat perlindungan dari kekerasan dan diskriminasi demi terwujudnya anak Indonesia yang berkualitas, berakhlak mulia dan sejahtera mutlak diperlukan untuk menjamin tumbuh kembang baik mental, spritual dan sosial. Pendidikan anak usia dini memberikan landasan pokok dan pembentukan karakter di masa emas anak dalam meniti kehidupan. Kurikulum dan metode pembelajaran yang baik dan menjamin diberikannya hak anak dan hak asasi manusia mutlak diberikan demi masa depan anak berupa non diskriminasi, kepentingan yang terbaik bagi anak, kelangsungan hidup dan perkembangan, penghargaan terhadap pendapat anak.